2021
DOI: 10.1016/j.trechm.2021.09.003
|View full text |Cite
|
Sign up to set email alerts
|

New trends in nonconventional carbon dot synthesis

Abstract: Carbon dots (CDs) are currently one of the hot topics in the nanomaterial world. Until recently, their preparation has been mostly based on solvothermal or hydrothermal syntheses requiring high temperatures, long reaction times, or toxic solvents. Moreover, the resulting materials are often affected by low reproducibility and difficult purification. A potential solution to these problems could be represented by innovative fields of chemistry, such as mechanochemistry, flow chemistry, and laser synthesis in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…Xie et al used a one-step hydrothermal method to synthesize nitrogen and silicon codoped fluorescent CDs with a product yield of 52.56% . However, the product yield of these CDs prepared by them is not high enough, and the disadvantages of the hydrothermal method are also obvious; the reaction temperature of the hydrothermal method was usually higher than 150 °C during the use of high-pressure reactors . Undoubtedly, high temperature and high pressure will cause great security risks.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al used a one-step hydrothermal method to synthesize nitrogen and silicon codoped fluorescent CDs with a product yield of 52.56% . However, the product yield of these CDs prepared by them is not high enough, and the disadvantages of the hydrothermal method are also obvious; the reaction temperature of the hydrothermal method was usually higher than 150 °C during the use of high-pressure reactors . Undoubtedly, high temperature and high pressure will cause great security risks.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon dots (CDs), as emerging luminescent nanomaterial, are now widely applied in biological, [18][19][20] optoelectronic, [21][22][23] and energy-related fields, [24][25][26] owing to their impressive optical properties, small size, low toxicity, easy preparation, and biocompatibility. [27][28][29] At present, most reported studies on the optical properties of CDs focus on fluorescence (FL). Few reports investigate the RTP properties of CDs, especially in matrix-free systems.…”
Section: Introductionmentioning
confidence: 99%
“… 29 31 Besides, recent interest in unconventional strategies for carbon nanodot fabrication attracted attention to this synthetic method. 32 To date, pulsed laser synthesis was only applied to homocyclic aromatic compounds, benzene or toluene, and produced nitrogen-free nanodots, hence the understanding of the nitrogen effect on the properties of CNDs produced by this method was lacking. In this work, we for the first time produced carbon nanodots by laser synthesis from a heterocyclic aromatic compound (pyridine), and also, to the best of our knowledge, synthesized nitrogen-doped CNDs from a compound where all carbon and nitrogen atoms belonged to the aromatic system.…”
Section: Introductionmentioning
confidence: 99%
“…Simple aromatic molecules are especially attractive in this context since their aromatic ring is a natural building block for constructing nanoparticles with a graphitic crystalline structure. A number of works demonstrated that intense optical fields of pulsed lasers are an effective instrument for the assembly of aromatic molecules into CNDs with characteristic excitation-dependent visible fluorescence. Besides, recent interest in unconventional strategies for carbon nanodot fabrication attracted attention to this synthetic method . To date, pulsed laser synthesis was only applied to homocyclic aromatic compounds, benzene or toluene, and produced nitrogen-free nanodots, hence the understanding of the nitrogen effect on the properties of CNDs produced by this method was lacking.…”
Section: Introductionmentioning
confidence: 99%